Optimum Design of a Five-phase Permanent Magnet Synchronous Motor for Underwater Vehicles by use of Particle Swarm Optimization - Reza Ilka; S. Asghar Gholamian (Universitas Ahmad Dahlan, 2012)
Permanent magnet synchronous motors are efficient motors which have widespread applications in electric industry due to their noticeable features. One of the interesting applications of such motors is in underwater vehicles. In these cases, reaching to minimum volume and high torque of the motor are the major concern. Design optimization can enhance their merits considerably, thus reduce volume and improve performance of motors. In this paper, a new method for optimum design of a five-phase surface-mounted permanent magnet synchronous motor is presented to achieve minimum loss and magnet volume with an increased torque. A multi-objective optimization is performed in search for optimum dimensions of the motor and its permanent magnets using particle swarm optimization. The design optimization results in a motor with great improvement regarding the original motor. Finally, finite element analysis is utilized to validate the accuracy of the design.